MENGENAL PROFIL KARAKTER BANGSA JEPANG MELALUI FILSAFAT GANBARU - Iriyanto Widi Suseno (Diponegoro University, 2018)
The title of this research is to Know the Japanese Character Profile. The purpose of this study is to determine the role of Ganbaru philosophy in the formation of the character of the Japanese nation. The concept of ganbaru; survive, never give up, and do the best, which is implemented on the daily behavior of Japanese society. With descriptive research method of analysis, can describe the elements forming the character of the Japanese nation. This research can show that ganbaru philosophy has been practiced in many aspects of Japanese society life to bring the nation of Japan forward in world level.Key words : Profile of character, philosophy Ganbaru, Japanese nation